Development of new approaches to sterility testing of heterologous serum products by membrane filtration method - S. M. Sukhanova; Z. E. Berdnikova (Биопрепараты: Профилактика, диагностика, лечение)
Reliable evaluation of blood products sterility is a very important and one of the most complex and critical control methods in the context of microbiological safety. The membrane filtration method that uses a closed-circuit system has, for many years, been the main and the most preferable sterility test method for all known medicinal products. However, Russian manufacturers perform sterility testing of heterologous serum products by direct inoculation method only. The present study was aimed at exploring the feasibility of performing sterility testing of heterologous serum products by membrane filtration. It was shown that sample preparation could be modified by dilution of samples to, on average, 1.5-2 times the initial volume with a sterile 0.9 % sodium chloride solution followed by membrane filtration at a geared-up rate which lowers protein sorption by the membrane filter. The study helped to determine the range of protein impact on the membrane when testing serum products according to the State Pharmacopoeia 13th ed. It was shown that various types of filter elements from mixed cellulose esters and Durapore® (PVDF) could be used to test serum products by membrane filtration with a protein impact range of up to 12 g of protein per membrane. The results of heterologous serum products sterility testing by direct inoculation method and by membrane filtration were found to be comparable. Adaptation of the procedure to protein-containing products makes it possible to perform sterility testing by a more reliable and modern method. The authors can recommend the incorporation of the above-cited test procedure into quality standards for products concerned together with the currently used direct inoculation method.